Efecto de la Adición de Chía sobre las Características Sensoriales, Físico-Químicas y Rendimiento de la Mortadela - Baño Ayala, Darío (2017)
The cooked meat products have a deficit of fiber, the main objective is to investigate nutritional and economic effects when replacing starch by chia flour in the mortadella, obtaining a contribution in dry "chia" basis of 23.79% proteins, 38.47% Crude fiber, 28.96% crude fat, 3.28% carbohydrates and 5.50% ash, demonstrating that chia is a complete and balanced food. For the preparation, several dosages were tested, the most significant being T3, which added 5% of chia flour, generating the following results: 33.71% in proteins, 5.27% in raw fiber, 52.59% in fat Crude, 0.02% in carbohydrates and 8.41% in ash, the raw fiber that increased from 0.07 in the control to 5,27 in the T3 treatment was highlighted. The acceptance was the one of less concentration for its color, for that reason 0.5 ml of red carmine was added per kilogram obtaining a similar coloration to the mortadela of the local brands Piggis and the Iberian.